Pengaruh Pajak Tangguhan dan Perencanaan Pajak Terhadap Kinerja Perusahaan - Fransiscus Felix Bhaktiar; Vinny Stephanie Hidayat (Universitas Kristen Maranatha, 2020)
This study aims to examine deferred tax and tax planning on company performance. This study has a population in the form of companies listed on the Indonesia Stock Exchange during the 2014-2018 period. The sampling technique used was purposive. In analyzing the data, the technique used was multiple regression, with a significance level of 5%. This study concludes that there is no partial or simultaneous influence between deferred tax and tax planning on company performance. Keywords: Deferred Tax, Tax Planning, Company Performance